Metabolic Effects of Acibenzolar-S-Methyl for Improving Heat or Drought Stress in Creeping Bentgrass - Jespersen, David; Yu, Jingjin; Huang, Bingru (Frontiers in Plant Science, 2017)
Acibenzolar-S-methyl (ASM) is a synthetic functional analogue of salicylic acid which can induce systemic acquired resistance in plants, but its effects on abiotic stress tolerance is not well known. The objectives of this study were to examine effects of acibenzolar-S-methyl on heat or drought tolerance in creeping bentgrass (Agrostis stolonifera) and to determine major ASM-responsive metabolites and proteins associated with enhanced abiotic stress tolerance. Creeping bentgrass plants (cv. ‘Penncross’) were foliarly sprayed with ASM and were exposed to non-stress (20/15°C day/night), heat stress (35/30°C), or drought conditions (by withholding irrigation) in controlled-environment growth chambers. Exogenous ASM treatment resulted in improved heat or drought tolerance, as demonstrated by higher overall turf quality, relative water content, and chlorophyll content compared to the untreated control. Western blotting revealed that ASM application resulted in up-regulation of ATP synthase, HSP-20, PR-3, and Rubisco in plants exposed to heat stress, and greater accumulation of dehydrin in plants exposed to drought stress. Metabolite profiling identified a number of amino acids, organic acids, and sugars which were differentially accumulated between ASM-treated and untreated plants under heat or drought stress, including aspartic acid, glycine, citric acid, malic acid, and the sugars glucose, and fructose. Our results suggested that ASM was effective in improving heat or drought tolerance in creeping bentgrass, mainly through enhancing protein synthesis and metabolite accumulation involved in osmotic adjustment, energy metabolism, and stress signaling.